Engineering Asset Management and Infrastructure Sustainability Proceedings of the 5th World Congress on Engineering Asset Management (WCEAM 2010) - Mathew, Joseph; Ma, Lin.; Tan, Andy.; Weijnen, Margot; Lee, Jay.; SpringerLink (Online service) (London : Springer London, 2012)
Engineering Asset Management 2010 represents state-of-the art trends and developments in the emerging field of engineering asset management as presented at the Fifth World Congress on Engineering Asset Management (WCEAM). The proceedings of the WCEAM 2010 is an excellent reference for practitioners, researchers and students in the multidisciplinary field of asset management, covering topics such as: Asset condition monitoring and intelligent maintenance Asset data warehousing, data mining and fusion Asset performance and level-of-service models Design and life-cycle integrity of physical assets Education and training in asset management Engineering standards in asset management Fault diagnosis and prognostics Financial analysis methods for physical assets Human dimensions in integrated asset management Information quality management Information systems and knowledge management Intelligent sensors and devices Maintenance strategies in asset management Optimisation decisions in asset management Risk management in asset management Strategic asset management Sustainability in asset management
Keywords: Engineering; Industrial engineering; Engineering economy; System safety; Telecommunication; Industrial organization (Economic theory).; Engineering; Engineering Economics, Organization, Logistics, Marketing; Industrial Organization; Industrial and Production Engineering; Signal, Image and Speech Processing; Communications Engineering, Networks; Quality Control, Reliability, Safety and Risk